Exact outage and intercept analysis of physical layer security in half-duplex energy harvesting relay systems - The-Anh Ngo; Xuan-Truong Tran; Viet-Thanh Le; Thien P. Nguyen; Duy-Hung Ha (Bulletin of Electrical Engineering and Informatics, 2026)
This paper investigates physical layer security (PLS) in a half duplex (HD) relay network with radio frequency energy harvesting (EH). We consider an amplify and forward (AF) protocol in which both the source and the relay harvest energy from a dedicated power beacon, while a passive eavesdropper attempts to intercept the confidential message. Unlike prior studies that rely on asymptotic analysis or numerical integration, we derive exact closed form expressions for the outage probability (OP) and the intercept probability (IP). The proposed expressions characterize the reliability and secrecy trade-off in energy limited cooperative relaying and enable efficient performance evaluation. Monte Carlo simulations validate the analysis and match the theoretical results. Moreover, the closed form results reveal how channel conditions and harvesting duration jointly shape outage and interception behaviors. We further quantify the impacts of normalized transmit power, the time allocation factor between harvesting and information transmission, and the EH efficiency. The results provide practical guidance for selecting system parameters to meet target reliability and secrecy levels, and they show that the time allocation factor must be carefully chosen to balance harvested energy and transmission time.